Nature and Culture: Environmental Issues in Asia - Palanca-Tan, Rosalina (Archīum Ateneo, 2014)
The chapters in this volume provide interesting cases of environmental constraints to development within sets of contrasting contexts—land-based resources versus water-based resources, local versus national government intervention policies and programs in resource preservations and rehabilitation, and developing versus developed country recipient of international disaster aid. The authors analyze the issues utilizing historical, sociological, and political lenses. The frameworks in these disciplines provide a rich blend of perspectives that shed light on the diverse modes of interplay between culture and nature and how they evolve together.